1990
DOI: 10.1172/jci114869
|View full text |Cite
|
Sign up to set email alerts
|

Two different point G to A mutations in exon 10 of the porphobilinogen deaminase gene are responsible for acute intermittent porphyria.

Abstract: Two mutations of the porphobilinogen (PBG) deaminase gene resulting in cross-reacting immunological material (CRIM) positive forms of acute intermittent porphyria (AIP) have been identified by in vitro amplification of cDNA and cloning of the amplified products in a bacterial expression vector. Both mutations resulted from G to A transitions in exon 10 of the gene and produced arginine to glutamine substitutions in the abnormal protein. Expression of mutant cDNA in Escherichia coli reveals that one but not the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 18 publications
2
36
0
Order By: Relevance
“…The identification and characterization of the mutations in the HMB-synthase gene causing ALP have increased our understanding of the molecular basis of variant AEP (22, 23), identified the molecular heterogeneity underlying both the classical and variant forms (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41), permitted the precise diagnosis of asymptomatic heterozygotes (22,23,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41), and opportunity for structure-function correlations of the human enzyme. Here, six new mutations in the HMB-synthase gene are described which further increase our understanding of the molecular basis of AIP and the synthesis, structure, and function of this heme biosynthetic enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The identification and characterization of the mutations in the HMB-synthase gene causing ALP have increased our understanding of the molecular basis of variant AEP (22, 23), identified the molecular heterogeneity underlying both the classical and variant forms (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41), permitted the precise diagnosis of asymptomatic heterozygotes (22,23,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41), and opportunity for structure-function correlations of the human enzyme. Here, six new mutations in the HMB-synthase gene are described which further increase our understanding of the molecular basis of AIP and the synthesis, structure, and function of this heme biosynthetic enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphoid cell lines were established and maintained as described previously (52). From each proband, erythrocyte lysates were assayed for HMB-synthase activity (21) and genomic DNA was extracted from peripheral blood (53,54) for detection of known HMB-synthase mutations (IVSI-1, IVSI+1, Q15SX, R167Q, R167W, R173Q, W198X, and IVSI2-1) as described previously (29)(30)(31)(32)(33)(34)(35).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four intragenic restriction fragment length polymorphisms (Msp I, Pst I, BstNI, and ApaLI) in the PBGD gene have been successfully used for haplotype analysis including carrier detection in AIP families (3)(4)(5). Several point mutations of the PBGD gene have been identified in phenotypically different AIP patients (6)(7)(8)(9). However, none ofthe mutations so far identified has been found to occur more frequently than any of the others.…”
mentioning
confidence: 99%
“…To date, more than 30 different mutations have been reported (Daimon et al, 1993(Daimon et al, , 1994Delfau et al, 1990Delfau et al, , 1991Grandchamp et al, 1989a-c;Gu et al, 1992Gu et al, , 1994Scobie et al, 1990;Lee and Anvret, 1991;Lee et al, 1990;Llewellyn et al, 1992;Lundin et al, 1994;Mgone et al, 1992Mgone et al, , 1993Schreiber et al, 1994). Although high prevalences have been reported for two mutations as the result of a founder effect (Lee et al, 1990;Lee and Anvret, 1991 ;Gu et al, 1993), many of them were found only in very few families, indicating that AIP is very heterogeneous at the molecular level.…”
mentioning
confidence: 99%